CMT352: Material Science / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2017)
The course is designed to introduce students to the principal topics in materials science emphasizing the role of materials in the general context of everyday applications and demonstrating the importance of materials science in improving quality of life. Lecture sessions employ a mixture of lectures, tutorials and group work (self and peer discussions). The outcomes shall be assessed through a variety of tools which include the paper examination, quizzes and assignments.